Social Class Conflict in the Novel Lan A’isha fi Jilbab Abi - Stasfa, Aida Dinda (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to examine the social class conflict in Ihsan Abdul Quddus’ novel "Lan A’isha fi Jilbab Abi." Through this study, the researcher analyzes the social class conflict within the novel, its causes, and its impact. The focus of this study is to examine how the conflict within Abdul Ghafur Al-Bar’i’s family arises due to the role of wealth and social standing. The results show that the father’s wealth actually creates internal conflict for his children. Of his six children, only one son and two daughters successfully navigate their social class conflict. Through this story, researchers can learn lessons about social class conflict and its solutions. Overall, this study concludes that the novel "Lan A’isha fi Jilbab Abi" not only depicts family conflict but also reflects the social conditions prevailing in society.